2008
DOI: 10.1016/j.physletb.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal asymmetry of direct photons in intermediate energy heavy-ion collisions

Abstract: Hard photon emitted from energetic heavy ion collisions is of very interesting since it does not experience the late-stage nuclear interaction, therefore it is useful to explore the early-stage information of matter phase. In this work, we have presented a first calculation of azimuthal asymmetry, characterized by directed transverse flow parameter F and elliptic asymmetry coefficient v 2 , for proton-neutron bremsstrahlung hard photons in intermediate energy heavy-ion collisions. The positive F and negative v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…More details of the model can be found in Refs. [11,17]. The probability for emitting a photon in a single p-n collision can be written as…”
Section: Re-extract Nucleon's Kinetic Energy Considering Dynamic mentioning
confidence: 99%
See 1 more Smart Citation
“…More details of the model can be found in Refs. [11,17]. The probability for emitting a photon in a single p-n collision can be written as…”
Section: Re-extract Nucleon's Kinetic Energy Considering Dynamic mentioning
confidence: 99%
“…frame and the velocity of the γ-emission source is close to half of the beam's velocity. Such a fact strongly suggests the incoherent proton-neutron (p-n) collision during the early stage of nuclear interaction is dominated for the hard photon bremsstrahlung [15][16][17][18][19]. Based on this mechanism, the inverse slope of hard photons could be taken as a measure of the energy and momentum distributions of nucleons which are responsible for hard photon production [2,3,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the TAPS collaboration has done a series of experiments investigating properties of hot and dense matter using hard photons as messengers [79][80][81][82]. Theoretically, it was concluded that neutron-proton bremsstrahlungs in the early stage of the reaction are the main source of high energy photons [83,84]. It was also demonstrated that hard photon productions in heavy-ion collisions can be used to probe the reaction dynamics leading to the formation of dense matter [85][86][87][88][89].…”
Section: The Brief Description Of the Updated Ibuu Transport Modelmentioning
confidence: 99%
“…However, compared with nucleons, light fragments and projectile-like fragments produced in the reaction, hard photons have a considerable advantage not being disturbed by the final-state interactions. Therefore, hard photons provide a clean probe of the reaction dynamics and deliver an unperturbed picture of the emitting source [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%